Cholinergic brainstem neurons modulate cortical gamma activity during slow oscillations. - Mena-Segovia, J; Sims, H; Magill, P; Bolam, J (2008)
Cholinergic neurons in the rostral brainstem, including the pedunculopontine nucleus (PPN), are critical for switching behavioural state from sleep to wakefulness, and their presumed inactivity during sleep is thought to promote slow cortical rhythms that are characteristic of this state. However, it is possible that the diminished activity of cholinergic brainstem neurons during slow-wave sleep continues to have a functional impact upon ongoing cortical activity. Here we show that identified cholinergic projection neurons in the PPN fire rhythmically during cortical slow oscillations, and predominantly discharge in time with the phase of the slow oscillations supporting nested gamma oscillations (30-60 Hz). In contrast, PPN non-cholinergic neurons that are linked to cortical activity fire in the opposite phase and independent of nested gamma oscillations. Furthermore, cholinergic PPN neurons emit extensive local axon collaterals (as well as long-range projections), and increasing cholinergic tone within the PPN enhances the nested gamma oscillations without producing sustained cortical activation. Thus, in addition to driving global state transitions in the cortex, cholinergic PPN neurons also play an active role in organizing cortical activity during slow-wave sleep. Our results suggest that the role of the PPN in sleep homeostasis is more diverse than previously conceived. The functions supported by nested gamma oscillations during sleep (i.e. consolidation, plasticity) are critically dependent on the gating of the underlying cortical ensembles, and our data show that cholinergic PPN neurons have an hitherto unappreciated influence on this gating process.